PHYSIOLOGY EFFICIECY OF NITROGEN ABSORBTION WITH THREE SOYBEAN VARIETY OF UREA AND APPLICATIONS RHIZOBIUM IN SOIL WITH NUTRITRIONAL STATUS LOW NITROGEN - Makruf Wicaksono (Jurnal Pertanian Tropik, 2015)
The use of chemical nitrogen fertilizer tends to be high on soils with low nitrogen nutrient status, it can affect the balance of the global N cycle, contamination of groundwater and the increasing N2O (nitric monoxide is one of the greenhouse gases). The objective of this research to compare the effect of nitrogen fertilization and application of Rhizobium on nitrogen uptake efficiency, growth and yield of three varieties of soybeans In Soil With Nutritional Status Low Nitrogen. The research was conducted at the practice field Agricultural Extention Collage Medan, Deli Serdang North Sumatra Province in August-December, 2014. The method used is split-slip plot design with the main plot Rhizobium application and without Rhizobium, the subplot is the varieties used are Burangrang, Tanggamus, and Wilis. The sub-sub plot is the standard of N fertilization, which is control, urea 50 kg/ha, 100 kg/ha and 150 kg/ha. Variable observations include nitrogen absorption, plant dry weight, nodule, and production. The results showed that the application of Rhizobium on the variety of Wilis provides a significant response to the increased absorption of nitrogen, whereas the varieties Burangrang and Tanggamus not give a significant response to increased nitrogen absorption. A urea fertilizer dose of 150 kg/ha on the use of Rhizobium inoculant tends to give a negative reaction to the Physiology Efficiency Of Nitrogen Absorbtion (PEN), nodule, and weight of 100 grains. Physiology Efficiency Of Nitrogen Absorbtion (PEN) of three varieties tested were not affected by the level of nitrogen fertilization and the addition of Rhizobium